A surrogate model for thermal characteristics of stratospheric airship. Issue 12 (15th June 2018) - Zhao, Da; Liu, Dongxu; Zhu, Ming
Highlights: A surrogate model for thermal characteristic stratospheric aerostat is proposed. The surrogate model based on LSSVR-GSA has great fitting and generalization ability. Pre-treated classification strategy plays a major role in improving model accuracy. Abstract: A simple and accurate surrogate model is extremely needed to reduce the analysis complexity of thermal characteristics for a stratospheric airship. In this paper, a surrogate model based on the Least Squares Support Vector Regression (LSSVR) is proposed. The Gravitational Search Algorithm (GSA) is used to optimize hyper parameters. A novel framework consisting of a preprocessing classifier and two regression models is designed to train the surrogate model. Various temperature datasets of the airship envelope and the internal gas are obtained by a three-dimensional transient model for thermal characteristics. Using these thermal datasets, two-factor and multi-factor surrogate models are trained and several comparison simulations are conducted. Results illustrate that the surrogate models based on LSSVR-GSA have good fitting and generalization abilities. The pre-treated classification strategy proposed in this paper plays a significant role in improving the accuracy of the surrogate model.